(untitled) (Inflexion Point Magazine, 2026)
This document presents the application of the topic of determining demand forecasts, which serves as a fundamental pillar in making decisions related to the planning and control of production, of any organization that works under a push production scheme. (make to stock), model under which most organizations operate. The case study corresponds to a company dedicated to the sale and distribution of hair and body products in different locations. Additionally, the balance point of each headquarters is determined, to establish the feasibility of the distributed brands, in terms of their participation in the gross and net profit. Initially, the sales data provided by the company for each of them are analyzed. It was found that the forecasting methods that adjust to the behavior of historical sales data are those that consider seasonality, but that they differ for the distribution points by applying the Winters method (for 3 of 4 points) and the seasonal method without trend. Given that sales occur with an increasing and similar seasonality each year. It was also identified that all locations are profitable for the organization, and which are the most relevant brands.